Using Intelligent Agents in Online Betting Management Systems - POPÎRLAN, Claudiu Ionut; GAVRILĂ, Laura; POPÎRLAN, Cristina (Journal of Advanced Research in Management, 2018)
In this paper we present the possibility of integration intelligent agents in online betting strategy, in order to increase profitability. We proposed this approach for a betting management system and examined its usefulness in the online betting market. We also compared the proposed model against other most commonly used prediction methods.